Digital Competencies of University Professors in the 21st Century - Novaković, Aleksandar M.; Ranđelović, Branislav M.; Đukić, Danijela P. (Collection of Papers of the Faculty of Philosophy in Priština, 2022)
The latest developments in education caused by the 2019-nCOV virus pandemic and the transition from traditional teaching to electronic teaching, have influenced the special interest of teaching methodologists in determining the digital competencies of teaching staff in the 21st century. The changes have especially "affected" university professors, from whom the professional public expects to be role models in the application of modern information and communication technologies. Those who previously understood the importance of computers and mobile phones in teaching went through the transition from one type of teaching to another more painlessly, while it was far more difficult for those who denied their functionality from the beginning. Such a factual situation has influenced a deeper understanding of their function in modernizing academic practice, analyzing official strategies for the development of education and the existing frameworks of necessary digital competencies. Therefore, the authors in this paper propose a framework for digital competencies of professors at higher education institutions in the Republic of Serbia, classifying them into six categories necessary for the successful implementation of academic teaching: 1) Basic information knowledge about modern information and communication technologies; 2) Creating accounts and using different online clients to establish communication in a virtual environment; 3) Managing a virtual learning environment; 4) Preparation of teaching materials with the help of application software; 5) Creating and managing an electronic portfolio; 6) Safe use of online environment and ethics.
Keywords: digital competencies; university professors; modern information and communication technologies; modernization of teaching